Influence of doping Zr on the performance of CeO2-ZrO2-Al2O3 composite oxide after reductive heat treatment - YANG Huang-gen; TAN Yu-fang; WEI Qing-min; YAN Quan; CHEN Yuan; ZHU Li-gang; QIN Li-qin; XIAO Yi-hong (Cailiao gongcheng, 2020)
Ceria-zirconia-alumina composite oxides CZxA (the molar ratios of Ce, Zr and Al are 1:x:2, x=0, 0.5, 1, 1.5 and 2) fresh samples were prepared by the co-precipitation method. The samples were thermally aged in a flowing air atmosphere and in 10% H2/Ar flow. The structure and performance of the composite oxides were studied by X-ray powder diffraction (XRD), N2 adsorption-desorption (BET), oxygen storage capacity (OSC) measurements, and H2 temperature-programmed reduction (H2-TPR). The results show that for CZxA samples, with the increase of the content of Zr, no CeAlO3 phase is observed in the CZ1.5A-H2-1100 and CZ2A-H2-1100 samples which are reductively aged at 1100 ℃; the oxygen storage capacity (OSC) is 713 μmol·g-1 and 548 μmol·g-1, respectively, far higher than the 23 μmol·g-1 of CZA-H2-1100; and the hydrogen consumption of H2-TPR is 1995 μmol·g-1 and 2087 μmol·g-1, respectively, while the hydrogen consumption of CZA-H2-1100 was significantly reduced to 310 μmol·g-1. The OSC of CZxA is affected by the formation of CeAlO3 during the reductive treatment, which is consistent with the change result of the hydrogen consumption of H2-TPR. It was found that CA samples are more likely to produce CeAlO3 after reductive treatment, and the CZ1.5A and CZ2A samples doped with a certain amount of Zr elements in CA can inhibit the formation of CeAlO3, thus significantly improve the oxygen storage performance and the hydrogen consumption of H2-TPR of the material. Furthermore, CZxA have better reduction performance at low temperature after reductive treatment.